URGENSITAS PENDIDIKAN DINIYAH (Upaya Pengembangan Pendidikan Islam di Indonesia) - Saiful Saiful (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2020)
ABSTRACT The existence of Religious Education is regulated in Minister of Religion Decree No.1 of 2001 which aims as an effort to develop Islamic education in Indonesia. Religious education aims to educate students become a generation of qualified and noble Muslims. It intends to train students mentally and spiritually so they have detailed and comprehensive knowledge of the Islamic religion. Religious education carried out at formal and non-formal institutions is an effort to develop Islamic education in Indonesia which is guided by the fundamental values contained in the Qur'an and Hadith. In addition, it is also as a controller of the current globalization that is so fast. Religious education is divided into three levels, namely (a) Diniyah Awaliyah education is for MI/ SD level education. (b) Diniyah Wustha education is for MTS / SMP level education. (c) Diniyah ‘Ulya education is for MA / SMA level education. The formal religious education curriculum includes: Civics, Bahasa, Mathematics, Natural Sciences and Cultural Arts. While, the non-formal religious education curriculum includes: Al-Qur'an, hadith, Aqeedah, Fiqh, History of Islamic Culture, Arabic language, and Practice of worship.Keywords: Urgensity, Religious Education, Islamic Education ABSTRAK Eksistensi Pendidikan Diniyah diatur dalam Keputusan Menteri Agama No.1 Tahun 2001 yang bertujuan sebagai upaya pengembangan pendidikan Islam di Indonesia. Pendidikan diniyah bertujuan mendidik santri menjadi generasi Islam yang berkualitas dan berakhlak mulia. Pendidikan diniyah bertujuan melatih mental dan spiritual anak didik sehingga memiliki pengetahuan agama Islam secara detail dan menyeluruh. Pendidikan diniyah yang dilaksanakan pada lembaga formal dan non formal merupakan upaya pengembangan pendidikan Islam di Indonesia yang berpedoman kepada nilai-nilai mendasar yang terkandung dalam al-Qur’an dan Hadits. Selain itu, pendidikan diniyah merupakan pengontrol terhadap arus globalisasi yang begitu cepat. Pendidikan diniyah terbagi kepada tiga jenjang, yaitu (a) Pendidikan diniyah awaliyah yaitu pendidikan tingkat MI/SD. (b) Pendidikan diniyah wustha, yaitu pendidikan tingkat MTS/SMP. (c) Pendidikan diniyah ‘ulya, yaitu pendidikan tingkat MA/SMA. Adapun kurikulum pendidikan diniyah formal meliputi: PKn, bahasa Indonesia, matematika, ilmu pengetahuan alam dan seni budaya. Sedangkan kurikulum pendidikan diniyah non formal meliputi: Al-Qur’an hadits, aqidah akhlak, fiqh, sejarah kebudayaan Islam, bahasa arab, dan praktek ibadah. Kata Kunci: Urgensitas, Pendidikan Diniyah, Pendidikan Islam